Treatment recommendation system - Nguyen P.T.; Ilayaraja M.; Shankar K.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
In health care service the treatment recommendation system is plays very important role. In health care services for decision making the Treatment Recommender Systems (TRS) presented as a complementary tools. In current process the Treatment Recommender Systems increase the technology usability and reduce overloading of information. BEIESP.